Bleeding Complications of a Tracheostomy Stoma Covid-19 Patients Related to Therapy Heparin - Adnan Abdullah; Asti Widuri (Universitas Ahmad Dahlan, 2021)
Tracheostomy measures will increase as the number of ICU patientsincreases. The main indication for tracheostomy in intensive carepatients is to reduce dead space and reduce the risk of laryngealdamage due to long-term intubation. In the era of the Covid-19pandemic, tracheostomy procedures require consideration of thebenefits for patients and the risk of spreading the virus thatendangers health workers. In this case, it is reported that theimplementation of a tracheostomy with a safe procedure in patientswith severe Covid-19 infection and complications of stoma bleeding6 days after the tracheostomy procedure with risk factors for theuse of heparin anti-coagulant drugs